An assessment of the random-phase approximation functional and characteristics analysis for noncovalent cation–π interactions. Issue 38 (18th September 2017) - Su, He; Wu, Qiyang; Wang, Hongyan; Wang, Hui
Abstract : The structure, binding energy, AIM, and RDG properties of noncovalent cation–π interactions are investigated systematically. We demonstrate that the random-phase approximation (RPA) functional can give an inexpensive description of noncovalent interactions in molecular clusters without sacrificing the accuracy compared to the high-level CCSD(T) method. Abstract : The binding energy is of great importance in understanding the formation and stability of noncovalent interactions. However, the determination of the binding energy with high precision and efficiency in medium- and long-range noncovalent interactions is still challenging for quantum chemistry. Here, we assess the performance of random-phase approximation (RPA), a fully non-local fifth-rung of the Jacob ladder functional, in determining the binding energy of cation–π systems (cation = Li +, Na +, Be 2+, Mg 2+, Al +, and NH4 + ; π = C6 H6 ), which, to the best of our knowledge, has not been investigated. Using experimental results as the benchmark, we systematically compared the RPA method to the other ab initio methods (DFT/B3LYP, MP2, CCSD(T), and QCISD(T)) both in calculation accuracy and efficiency. From the perspective of accuracy, RPA is the best among these approaches, followed by the CCSD(T) and QCISD(T) methods. DFT/B3LYP and MP2 provide the worst accuracy. In addition, the computational efficiency of RPA is much faster than that of CCSD(T) and QCISD(T). We believe that RPA is a robust method for the precise description of medium- and long-range noncovalent interactions and is capable of providing benchmarking data. The interaction strength and interaction nature of cation–π systems are further analyzed by atoms in molecules (AIM) and the color-mapped reduced density gradient (RDG) isosurface, which are consistent with the characteristics of a typical cation–π interaction.